2022
DOI: 10.1111/phn.13075
|View full text |Cite
|
Sign up to set email alerts
|

Social vulnerability indicators in pandemics focusing on COVID‐19: A systematic literature review

Abstract: Introduction Social factors can affect the vulnerability of disaster‐prone communities. This review aimed to identify and categorize social vulnerability indicators in the COVID‐19 pandemic. Methods This systematic review was conducted in February 2021. Bibliographies, citation databases, and other available records were investigated based on the aim of the study. The Joanna Briggs Institute (JBI) critical appraisal tools were applied for assessing the included articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 72 publications
1
16
0
Order By: Relevance
“…These dashboard data could also reveal potential problems and biases in what was being reported, especially as testing became less widespread in later 2021 and 2022. Most notably, areas with high social vulnerability scores in the large urban centers would map as having little disease which is counter to what is expected [ 26 , 27 , 28 ]. The erroneous map interpretation of these cold spots would have been that the more susceptible areas were being spared, whereas the reality was the map pattern was showing where there were testing deficiencies ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 77%
“…These dashboard data could also reveal potential problems and biases in what was being reported, especially as testing became less widespread in later 2021 and 2022. Most notably, areas with high social vulnerability scores in the large urban centers would map as having little disease which is counter to what is expected [ 26 , 27 , 28 ]. The erroneous map interpretation of these cold spots would have been that the more susceptible areas were being spared, whereas the reality was the map pattern was showing where there were testing deficiencies ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 77%
“…This study was carried out after successive waves of the pandemic to harness the available information. It has a focus on measures related to agility in government response to implement non-pharmacological measures [ 11 ], social vulnerability [ 24 ] and combines several epidemiological and socioeconomic indicators in line with what has been suggested by other studies [ 3 , 10 , 25 ] but with a greater number of variables in the algorithms. We have included information from different time points in order to provide a better understanding of the socioeconomic variables around the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…This remains controversial, as some authors have found similar results [ 10 , 25 ] and others have found differences between deprived and more wealthy areas [ 29 ]. However, a systematic review that included domains and variables of social vulnerability affecting COVID-19 such as population aged 65 years or older, unemployment rate, population living below poverty line and public health infrastructures found that higher social vulnerability experienced greater mortality rates during the COVID-19 pandemic [ 24 ]. The growth of per capita debt and the number of cases followed a similar trend, although this relationship was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, providing financial subsistence support packages could have a significant effect on reducing public commuting but finally, poor support policies and social factors by the government caused people to defy the restrictions, which ultimately contributed to increase rate of infection and mortality. Further, social factors caused psychological problem, depression and violence among people [ 36 ]. These findings are consistent with the results of a study conducted in Santiago, Chile in 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have examined the effects of social distance on the living conditions of various people as children, pregnant women, the elderly and patients during the corona epidemic period [ 25 31 ]. Moreover in some essays the effect of quarantine and distance on the incidence of social anomalies and behavioral problems has been stated [ 32 36 ]. In another essay, researchers have examined the social and economic factors of the COVID epidemic in 42 Asian countries empirically.…”
Section: Introductionmentioning
confidence: 99%